Innovation and application of inter-provincial carbon emission transfer accounting model in China’s domestic production network - YANG, Puhang; YANG, Yong (Frontiers in Environmental Science, 2024)
The New Development Paradigm will result in the significant development of domestic production networks and the accelerated growth of carbon transfers among provinces in China. However, the existing trade of intermediate goods decomposition method cannot completely account for the carbon content of intermediate goods. So the paper developed a accounting model for inter-regional intermediate goods trade. The most significant advantage of it is that by further decomposing final output into three components-final consumption within the region, final consumption flowing to other regions, and final output flowing to other regions as intermediate goods that are not returned to the region-it achieves a more comprehensive decomposition of the value chain in comparison to the established models. This approach allows for tracking longer value chains, accounting for intermediate goods inflows and outflows simultaneously, and can be conducted for any number of countries, regions, and sectors, thereby providing a foundation for the comprehensive accounting of inter-regional carbon transfers within production networks. With the input-output tables and carbon emission inventories from the CEADs, the paper has calculated the changes of the carbon transfer among provinces in the China's domestic production network from 2012 to 2017 and find that the carbon transfer among provinces is increasing significantly. Each province has a strong incentive to overuse the carbon embodied in the intermediate goods from others, but lacks the motivation to reduce their own carbon emission. The difference between the average value of the ratio of the carbon content of intermediate goods from other provinces used by each province and that supplied for use by other provinces to the ratio of the carbon content of intermediate goods produced by itself increased by 13.6% from 2012 to 2017. Only a few provinces are evolving towards a win-win between economic and environmental benefits, while most are still facing the evolutionary dilemma. We should comprehensively explore the cooperative governance of carbon emission reduction in the domestic production network, including establishing a national standard for calculating the carbon transfer in domestic production network, improving the carbon emission responsibility sharing mechanism and carbon emission reduction compensation systems.